2013
DOI: 10.1038/emboj.2013.243
|View full text |Cite
|
Sign up to set email alerts
|

Divergent roles of HDAC1 and HDAC2 in the regulation of epidermal development and tumorigenesis

Abstract: The histone deacetylases HDAC1 and HDAC2 remove acetyl moieties from lysine residues of histones and other proteins and are important regulators of gene expression. By deleting different combinations of Hdac1 and Hdac2 alleles in the epidermis, we reveal a dosage-dependent effect of HDAC1/HDAC2 activity on epidermal proliferation and differentiation. Conditional ablation of either HDAC1 or HDAC2 in the epidermis leads to no obvious phenotype due to compensation by the upregulated paralogue. Strikingly, deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 53 publications
(98 reference statements)
5
52
2
Order By: Relevance
“…Whereas the effect of HDAC inhibitors used in the treatment of solid tumours are disappointing 43,44 , it has also been shown that HDAC inhibitors can induce EMT in prostate cancer cells 45 . HDAC1 and HDAC2 have been reportedly shown to function as tumour suppressors in epidermis and lymphomas [46][47][48] . In this study, we also showed that HDAC1 is a negative regulator of Smad2 and Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the effect of HDAC inhibitors used in the treatment of solid tumours are disappointing 43,44 , it has also been shown that HDAC inhibitors can induce EMT in prostate cancer cells 45 . HDAC1 and HDAC2 have been reportedly shown to function as tumour suppressors in epidermis and lymphomas [46][47][48] . In this study, we also showed that HDAC1 is a negative regulator of Smad2 and Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Hdac1 and Hdac2 redundantly regulate various cellular and developmental processes, including cardiac morphogenesis, adipogenesis, brain development, intestinal homeostasis, proliferation, and stem-cell self-renewal (Montgomery et al, 2007; Montgomery et al, 2009; Haberland et al, 2010; Jurkin et al, 2011; Jamaladdin et al, 2014; Zimberlin et al, 2015). In some cases, a single allele of Hdac1 or Hdac2 is enough to rescue the double knockout phenotype (Dovey et al, 2013; Winter et al, 2013; Hagelkruys et al, 2014). While the developmental roles of Hdac1 and Hdac2 are emerging, their function in NC progenitor cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the safety of the HDAC inhibitors is a significant concern because HDAC1 and HDAC2 also play important roles in regulating gene expression in development. Loss of HDAC1 and HDAC2 led to profound defects in tissues with epithelial structures, such as intestine and epidermis (Brunmeir et al, 2009; Gonneaud et al, 2015; Winter et al, 2013). Furthermore, the enzymatic activities of HDAC1 and HDAC2 are dependent on their incorporation into different protein complexes, such as the Sin3, NuRD and CoREST complexes, which bind and deacetylate distinct substrates (Kelly and Cowley, 2013; Moser et al, 2014).…”
Section: Introductionmentioning
confidence: 99%